2020
DOI: 10.20344/amp.12075
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Radiology Test Requests by an Emergency Department: A Retrospective Study

Abstract: Introduction: Imaging tests are essential for diagnosis in the emergency context and convey clinical information that is essential to assess the appropriateness of the tests and improve their interpretation. Therefore, we aimed to analyze the imaging tests requested by the Emergency Department in a district hospital.Material and Methods: We retrospectively analyzed computed tomography and ultrasound scans requested by the Emergency Department at the Centro Hospitalar Universitário do Algarve and considered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…A systematic review focusing on cardiovascular pathology showed that between 7 and 23% of transthoracic echocardiograms performed were considered inappropriate; between 28 and 30% of stress echocardiograms were classified as inappropriate, together with 9% to 44% of cardiac CT studies and 4% to 46% of SPECT studies [20]. Moreover, a study which evaluated the appropriateness of imaging test requests in an emergency department showed that only 15.3% of the requests contained sufficient clinical information, a slightly higher percentage than that found in our own study [21].…”
Section: Discussioncontrasting
confidence: 63%
“…A systematic review focusing on cardiovascular pathology showed that between 7 and 23% of transthoracic echocardiograms performed were considered inappropriate; between 28 and 30% of stress echocardiograms were classified as inappropriate, together with 9% to 44% of cardiac CT studies and 4% to 46% of SPECT studies [20]. Moreover, a study which evaluated the appropriateness of imaging test requests in an emergency department showed that only 15.3% of the requests contained sufficient clinical information, a slightly higher percentage than that found in our own study [21].…”
Section: Discussioncontrasting
confidence: 63%
“…Martins et al reported a 23.8% rate of inappropriate CTs and US (for all causes) in the ED, using the ACR guidelines as standard-of-care. 7 In that study, only 33.9% of all tests performed showed relevant findings. Similarly, overuse of head CT for minor head injury is also well reported in the literature, with inappropriate rates ranging from 30%-70% of cases.…”
Section: Discussionmentioning
confidence: 75%
“…Sample size was calculated for an estimated proportion of inappropriate tests of 25% based on the results of previous studies. 7,8 Using a margin of error of 0.075, a 95% confidence interval (95% CI), and a 20% expected rate of subjects with incomplete clinical information for the appropriateness of a test to be determined, the final sample size required was 154 patients for each imaging modality. Continuous variables are expressed as mean § SD and comparisons were performed using two-sample, two-tailed Student's t-test.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown flaws of practitioners in filling of radiological request forms [ 18 , 19 ]. An analysis of request forms from a previous study showed that a significant proportion of requests forms had no clinical information [ 20 ]. It was established that clinicians who request an imaging examination frequently experience several difficulties in getting the clinical history of the patient, mainly due to little/no information described in clinical records of patients and delay in laboratory results [ 20 ].…”
Section: Discussionmentioning
confidence: 99%